2021
DOI: 10.53400/mimbar-sd.v8i1.26491
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teacher Education Students’ Short Story Writing Skills through Creative Writing Learning for Short Movie Making

Abstract: Short story writing skill (short stories) for elementary teacher education students at Cimahi City campus is one of the productive language skills that are said to be still very difficult, considering the skill to write requires multi skills  that involve cognitive skills, cognitive meta, experience, imagination, and the preparation of words and sentences accordingly. Hence, this digital era should be able to make students skilled in utilizing digital devices and products as a medium that helps facilitating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Short stories are commonly shorter and have fewer characters than novels (Anggitasari et al, 2020). Although a short story is shorter than a novel, previous research found that some learners encountered difficulties when reading a short story (Fauzi & Pratama, 2021;Janssen & Braaksma, 2018). The level of difficulty of a literary work can be measured.…”
Section: Introductionmentioning
confidence: 99%
“…Short stories are commonly shorter and have fewer characters than novels (Anggitasari et al, 2020). Although a short story is shorter than a novel, previous research found that some learners encountered difficulties when reading a short story (Fauzi & Pratama, 2021;Janssen & Braaksma, 2018). The level of difficulty of a literary work can be measured.…”
Section: Introductionmentioning
confidence: 99%